Identifikasi Root Cause Produk NG Master Cylinder di PT X - Suryawan, Lazuardi Allan; Sena, Boni; Rahmanto, Achmad Azis (Politeknik Negeri Padang, 2025)
The braking system is a crucial component in vehicles, responsible for reducing speed or halting the vehicle safely. However, several technical issues, such as brake fluid leakage, can compromise braking performance. Leaks can occur in hydraulic lines, the master cylinder, or brake calipers, leading to reduced hydraulic pressure and ineffective braking. Other issues like wear on components, excessive heat causing fading, and corrosion or contamination of brake fluid further degrade braking performance. The master cylinder plays a vital role in converting mechanical pressure into hydraulic pressure to operate the brake caliper. Damages such as fluid leaks, wear, corrosion, or contamination can impair this function, increasing the risk of accidents. Factors contributing to failures include poor material quality, machine setting errors, and inadequate maintenance. Regular inspection and maintenance of these components are essential to ensure vehicle safety and optimal braking performance.